The Paradox Between Environmental Protection and Zero Percent Coal Royalties in Law Number 11 of 2020 Concerning Job Creation - Dame Maria Silaban (Journal Social Civilecial, 2026)
This article examines the normative paradox between environmental protection and the 0% coal royalty policy in Indonesia’s coal downstreaming framework. Coal is a non-renewable natural resource controlled by the State and must be used for the greatest prosperity of the people. However, coal mining creates serious environmental risks, including land degradation, water pollution, mine voids, biodiversity loss, and long-term post-mining restoration burdens. Using normative juridical research, this article analyzes statutory regulations, legal principles, and doctrinal concepts related to state control over natural resources, non-tax state revenue, coal royalties, and environmental responsibility. The findings show that coal royalty has a dual function. It serves as a source of non-tax state revenue and as a regulatory instrument that connects coal extraction with public welfare and ecological accountability. The 0% royalty policy may encourage downstreaming and domestic added value, but it does not remove the environmental impacts of coal extraction. This policy may weaken state revenue, reduce fiscal capacity for environmental restoration, and create unequal distribution of benefits and burdens between mining companies, affected communities, and future generations. The article argues that Indonesia should avoid broad royalty exemptions and adopt a more proportionate model. The ideal legal construction should maintain a minimum royalty, apply conditional and performance-based incentives, require environmental restoration contributions, strengthen data transparency, and improve revenue allocation for mining regions. Such a model would better align coal downstreaming with constitutional mandates, sustainable development, environmental protection, and social justice.